Robotic resection of a single adenoid cystic tumor liver metastasis using ICG fluorescence. A case report and literature review - Pasquale, Alessio; Marinelli, Laura; Ciarleglio, Francesco Antonio; Campora, Michela; Salimian, Nick; Viel, Giovanni; Brolese, Alberto (Frontiers in Surgery, 2023)
Adenoid cystic carcinoma (AdCC) is a rare tumor that typically develops in the salivary glands and less frequently in other sites of the head and neck region. Only a few cases of resected metachronous liver metastases have been reported. Minimally invasive surgery is currently the gold standard of care for liver resections; furthermore, the use of Indocyanine Green (ICG) is continuously increasing in surgical practice, especially in cases of primary liver tumors and colorectal liver metastases, due to its capacity to enhance liver nodules. We report the case of a 54-year-old male with a single liver metastasis of AdCC, located in SIII, who presented in our center 9 months after resection of a primary tumor of the laryngotracheal junction and adjuvant proton therapy. A 25-mg injection of ICG (0.3 mg/kg) was administered 48 h before surgery in order to highlight the tumor and perform an ICG-guided resection. The lesion was clearly visible during surgery, and, given its position and the proximity to the main lobar vessels of the left lobe, we opted for a left lateral sectionectomy. The outcome was unremarkable, with no major postoperative complications. The administration of ICG 48 h before surgery seems to be a valid tool even in cases of AdCC liver metastases, providing surgeons with better visualization of the lesion and improving the precision of the resection.